The EFFECT OF BRAND TRUST, E-WOM, AND E-SERVICE QUALITY ON MAYBELLINE COSMETICS BUYING INTEREST AMONG SHOPEE MALL USERS IN SIDOARJO: PENGARUH BRAND TRUST, E-WOM, DAN E-SERVICE QUALITY TERHADAP MINAT BELI KOSMETIK MAYBELLINE PADA PENGGUNA SHOPEE MALL DI SIDOARJO - ZUHRIYAH, ISMATUL; Oetarjo, Mas; Pebrianggara, Alshaf (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This study aims to analyze the influence of Brand Trust, Electronic Word of Mouth (E-WOM), and E-Service Quality on Purchase Interest of Maybelline cosmetics at Shopee Mall, especially among users in Sidoarjo. This observation uses a quantitative approach, data was collected through an online questionnaire with 100 respondents. The independent variables analyzed were Brand Trust, E-WOM, and E-Service Quality, while the dependent variable was purchase interest. Data were analyzed using multiple linear regression methods through SPSS. The results showed that the three independent variables had a positive as well as significant influence on purchase interest. E-WOM had the greatest influence, followed by Brand Trust and E-Service Quality. This emphasizes the importance of positive online reviews and brand trust in increasing consumer interest.